Analisis Indeks Kekeringan Hidrologi DAS Krueng Aceh (Studi Kasus Sub DAS Krueng Jreue dan Sub DAS Krueng Khee) - Attabari Aldin; Hairul Basri; Syahrul Syahrul (Department of Agricultural Engineering, Syiah Kuala University, 2022)
Abstrak. Luas Sub DAS Krueng Jreue 23.218,06 Ha dan Sub DAS Krueng Khee 9.599,66 Ha. Berdasarkan hasil kajian bahwa luas vegetasi tutupan lahan semakin berkurang setiap tahunnya dimana ditandai dengan tingginya nilai fluktuasi debit sehingga mengakibatkan banjir pada musim hujan dan kekeringan pada musim kemarau. Tujuan penelitian adalah untuk mengetahui nilai ambang batas kekeringan hidrologi di Sub DAS Krueng Jreue dan Sub DAS Krueng Khee dan indeks kekeringan hidrologi di Sub DAS Krueng Jreue dan Sub DAS Krueng Khee. Penelitian ini menggunakan metode ranking Weibull dimana ditentukan nilai ambang batas Q50 dan Q80, dihitung defisit dan durasi dan kemudian ditentukan nilai indeks kekeringan hidrologi. Nilai ambang batas Sub DAS Krueng Jreue adalah 0,067 m3/s dan Sub DAS Krueng Khee 0,181 m3/s. Defisit Sub DAS Krueng Jreue tahun 2014 adalah tertinggi dengan angka 0,401 m3/s dengan durasi kering tujuh bulan dan Sub DAS Krueng Khee tahun 2012 adalah tertinggi dengan angka -0,715 m3/s dengan durasi kering enam bulan. Indeks kekeringan hidrologi di Sub DAS Krueng Jreue tahun 2015 adalah tertinggi dengan nilai 0,0629 m3/s dan indeks kekeringan hidrologi di sub DAS Krueng Khee tahun 2011 adalah tertinggi dengan nilai 0,3282 m3/s.An Analysis of The Krueng Aceh’s Hydrological Drought Index (A Case Study of The Sub Watershed Krueng Jreue and Krueng Khee)Abstract. The area of the Krueng Jreue Sub-watershed is 23,218.06 Ha and the Krueng Khee Sub-watershed is 9,599.66 Ha. Based on the results of the study that the area of land cover vegetation decreases every year which is indicated by the high value of discharge fluctuations, resulting in flooding in the rainy season and drought in the dry season. The purpose of this study was to determine the threshold value for hydrological drought in the Krueng Jreue Sub-watershed and Krueng Khee Sub-watersheds and the hydrological drought index in the Krueng Jreue Sub-watershed and Krueng Khee Sub-watersheds. This study uses the Weibull ranking method where the threshold values for Q50 and Q80 are determined, the deficit and duration are calculated and then the hydrological drought index value is determined. The threshold value for the Krueng Jreue Sub-watershed is 0.067 m3/s and the Krueng Khee Sub-watershed is 0.181 m3/s. The Krueng Jreue Sub-watershed deficit in 2014 was the highest at 0.401 m3/s with a dry duration of seven months and the Krueng Khee Sub-watershed in 2012 was the highest at -0.715 m3/s with a dry duration of six months. The hydrological drought index in the Krueng Jreue Sub-watershed in 2015 was the highest with a value of 0.0629 m3/s and the hydrological drought index in the Krueng Khee Sub-watershed in 2011 was the highest with a value of 0.3282 m3/s.